An above real time training intervention for sport decision making - Lorains, M.; Ball, K.; MacMahon, C. (Psychology of Sport and Exercise, 2013)
Objectives: A speeded video-based decision-making training intervention was used to assess the impact of above real time training on decision-making skill in sport. Design and methods: Three groups completed pre tests and either five weeks of fast speed video training, normal speed video training or no training, followed by a post test and two retention tests in subsequent weeks. Decision accuracy was measured by awarding three, two, one, or no point(s) based on independent coach ratings of each situation. Results: Results revealed that those trained in above real time improved performance earlier in the training intervention compared to those trained in normal speed. The above real time group also retained more of the performance improvements. The transfer test for decision accuracy showed improvement following the training intervention for all groups, trends in the data reflected a higher retention rate for the fast speed group choosing the bet option more frequently than normal and control groups. Conclusions: The results lend support to the general use of video-based decision-making training for team invasion sports. A greater impact is that they provide a new paradigm by adapting above real time training to decision making, to create a more game-like training scenario.